Peningkatan Pemahaman Teks Narasi Melalui Pengembangan Media Digital Berbasis Microsite di SDN Paron Kediri - Yusana, Ita; Ahmad Fauzi; Ali Imron (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2026)
This study aims to improve students’ narrative text comprehension through the development of microsite-based digital learning media. The background of this research is the low reading interest and limited comprehension ability among elementary students, caused by monotonous and less interactive learning media. This study used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research involved fourth-grade students at SDN Paron, Kediri Regency, with six students participating in the limited trial. The product was validated by material, media, and language experts. Results show that the media is valid, practical, and effective. Students' reading comprehension improved significantly, as indicated by the increase in posttest scores. Moreover, students gave a positive response to the media, with a satisfaction rate of 95% categorized as “excellent.” Therefore, microsite-based media is recommended as an innovative learning tool to support literacy and enhance reading comprehension in elementary education.